PERAN PENDIDIKAN ISLAM DALAM PEMBENTUKAN KARAKTER GENERASI MUDA - Perangin-Angin, Sri Levinia; Daulay, Zil Rahmi (Proceeding International Seminar of Islamic Studies, 2024)
This article discusses the importance of Islamic education in building the character of the younger generation. Because today many young generations are entangled in things that are not in accordance with the desired character in Islam. This study aims to explore and analyze the role of Islamic education in the formation of the character of the younger generation. Through a qualitative approach, this study investigates the implementation of Islamic values in the educational curriculum, the influence of the school environment and Islamic society, and the role of teachers as character-building agents. The findings show that Islamic education plays a central role in shaping the morals, ethics, and personality of the younger generation. By understanding and internalizing Islamic teachings, it is hoped that the younger generation can become pillars of society with integrity and contribute positively.